Risk of cryptorchidism and hypospadias among boys of maternal hairdressers - a Danish population-based cohort study - Kristian Tore Jørgensen; Morten Søndergaard Jensen; Gunnar Vase Toft; Ann Dyreborg Larsen; Jens Peter Bonde; Karin Sørig Hougaard (Nordic Association of Occupational Safety and Health (NOROSH), 2013)
OBJECTIVES: Pregnant hairdressers may be exposed to a mixture of chemicals in their working environment. The possible relationship between these chemical agents and male reproductive tract malformations has raised concern that the working environment of hairdressers might have adverse effects on fetal development. This study assessed the risk of cryptorchidism and hypospadias among boys of maternal hairdressers. METHODS: National population-based registers were used to determine maternal occupation and identify cases of cryptorchidism and hypospadias. The cohort comprised all children born in Denmark from 1980-2007. Using Cox regression, we estimated hazard ratios (HR) with 95% confidence intervals (95% CI) for hospitalization for cryptorchidism and hypospadias from 1980-2009. RESULTS: Boys of hairdressers were not at increased risk of cryptorchidism (134 cases, HR 0.91; 95% CI 0.77-1.08) or hypospadias (33 cases, HR 1.27; 95% CI 0.90-1.79) compared to children of mothers in other occupations (14 988 and 2556 cases of cryptorchidism and hypospadias, respectively). Additional analyses using children of shop assistants and receptionists as controls and restricted to (i) firstborns, (ii) cryptorchidism cases with corrective surgery, (iii) specific birth years, and (iv) women without social benefit payments in gestational weeks 8-14 produced consistent results of no increased risk. CONCLUSION: Our nationwide cohort study shows that, despite exposure to a complex chemical milieu, hairdressers do not have an increased risk of having boys with cryptorchidism and hypospadias.